Mikroba Tanah sebagai Kunci Pertanian Organik Berkelanjutan : Kajian Literatur - Harefa, Destri Natalis; Lase, Natalia Kristiani (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Organic farming has increasingly become a preferred choice in sustainable agricultural systems due to its significant benefits for environmental balance and quality. One of the key elements in organic farming is soil microorganisms, which play a crucial role in enhancing soil fertility and supporting plant health. Soil microorganisms, such as nitrogen-fixing bacteria, phosphate-solubilizing microbes, mycorrhiza, and organic matter decomposers, contribute significantly to fertilization efficiency and nutrient availability, as well as improving plant resistance to pathogens. The utilization of soil microorganisms as biofertilizers can reduce dependency on chemical fertilizers, mitigate environmental pollution, and increase agricultural productivity sustainably. Furthermore, soil microorganisms can improve soil structure, extend root longevity, and stimulate plant growth. The selection of appropriate microorganisms according to soil conditions and intended use is essential to maximize their benefits. Therefore, the application of soil fertility-promoting microorganisms as part of sustainable agricultural technology holds great potential to enhance environmentally friendly and efficient agricultural outcomes.